Neutrality as a Basis for Minority Cultural Rights - Lister, Andrew (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2015)
This comment examines the idea of ‘neutrality of treatment’ that is at the heart of Alan Patten’s defense of minority cultural rights in Equal Recognition. The main issue I raise is whether neutrality of treatment can do without an ‘upstream’ or foundational commitment to neutrality of justification.